APPLIED COMPONENT OF THE THEORY OF DIFFERENTIAL EQUATIONS IN PROBLEMS OF MECHANICS - Аршава, Елена (SWorldJournal, 2022)
The implementation of interdisciplinary integration of higher mathematics and theoretical mechanics is an urgent problem of the modern technical university. It is this approach in teaching academic disciplines that ensures the relationship between them bo